2018
DOI: 10.20473/mog.v25i32017.77-80
|View full text |Cite
|
Sign up to set email alerts
|

Dominant factors affecting uterine prolapse in Dr. Moewardi Hospital, Surakarta, in 2013-2015

Abstract: Objectives: To determine the dominant factors that affected uterine prolapse at Dr. Moewardi General Hospital Surakarta.Materials and Methods: This study was conducted to 259 cases of uterine prolapse at Dr. Moewardi Hospital, Surakarta, in the periods of January - December in the years 2013-2015. This was a correlational quantitative analytic study using chi-square test and regression analysis.Results: Factors affecting uterine prolapse were parity (p=0.024), age (p=0.036) and occupation (p=0.039). Parity had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…Women who've got history of giving birth 2 times, they have to deal with an increasing probability to suffer POP 3 times higher than those who have never given birth. 8,10,11 Vaginal delivery has a significant role in the POP incident, women who had undergone vaginal delivery, they are at risk of suffering from pelvic organ prolapse stage 2 or higher. 8,[11][12][13][14] The Pessary offers high effectiveness and efficient way to overcome POP, beside of its positive profile, pessary users have to deal with the probability of suffering bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who've got history of giving birth 2 times, they have to deal with an increasing probability to suffer POP 3 times higher than those who have never given birth. 8,10,11 Vaginal delivery has a significant role in the POP incident, women who had undergone vaginal delivery, they are at risk of suffering from pelvic organ prolapse stage 2 or higher. 8,[11][12][13][14] The Pessary offers high effectiveness and efficient way to overcome POP, beside of its positive profile, pessary users have to deal with the probability of suffering bacterial vaginosis.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 Vaginal delivery has a significant role in the POP incident, women who had undergone vaginal delivery, they are at risk of suffering from pelvic organ prolapse stage 2 or higher. 8,[11][12][13][14] The Pessary offers high effectiveness and efficient way to overcome POP, beside of its positive profile, pessary users have to deal with the probability of suffering bacterial vaginosis. 3 This research revealed that the probability was 5.9, and another research which had done by Alnaif&Drutz, it stated that the probability from suffering bacterial vaginosis for those who used pessaries was 4.37.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Menurut laporan tahunan Rumah Sakit Dr. Hasan Sadikin Bandung didapatkan prevalensi prolapsus organ panggul sebesar 20%, sedangkan penelitian di Rumah Sakit Dr. Moewardi Surakarta dari tahun 2013-2015 didapatkan 258 pasien dengan prolapsus uteri. 3 Faktor risiko terjadinya POP bersifat multifaktorial antara lain paritas, persalinan pervaginam, usia, obesitas, kelainan jaringan ikat, status menopause, dan konstipasi kronis yang menyebabkan kelemahan pada otot dasar panggul. Penyebab terjadinya POP memang multifaktorial, namun kehamilan merupakan faktor risiko utama yang paling umum.…”
Section: Pendahuluanunclassified
“…dihubungkan dengan kejadian prolaps organ panggul (Anggraeni, Wulansari, 2017). Persalinan menyebabkan regangan yang lama pada ligamentum sacrouterina dan otot levator ani (Dewan, 2021) sehingga memunculkan efek kerusakan sokongan organ pelvis (Razzak, 2018).…”
unclassified